Adoption of the N. Kano Model of Consumer Needs to the Service Market Segmentation and Product Differentiation - Žemgulienė, Jolanta; Zaleskytė, Jūratė (Ekonomika, 2002)
Different approaches towards the service product are discussed by great variety of authors. Most of the authors use to define product in two different ways - generically or psychologically. Describing the product generically product becomes a combination of physical and chemical properties. Services are described similarly in terms of functions to be performed by the firm that renders them. The psychological view holds that a product is not a physical entity but a perception of a physical entity by the consumer according to consumer needs and wants. Modem marketing and management theories emphasise the concept of the product as the combination of engineering attributes and experiential attributes. Satisfaction of consumer needs and customer’s performance expectations result in perceived consumer benefits. Different consumer needs does not have the same impact on consumer satisfaction. Therefore the methods of evaluation of consumer needs are of great importance for the development and innovation of the service product according to the consumer needs. The N. Kano model identifies three types of needs according to consumer satisfaction - basic, satisfier, delighter. The needs named as delighter has the potential for producing large returns for little effort made by the service company in order to achieve these needs. This model of consumer needs has been used as the service design technique.The basic focus of the article is introduction of N. Kano model of consumer needs as the instrument for market segmentation and product differentiation in the hotel service industry. The hypothesis of the research is possibility to introduce the delighter consumer needs as the criteria for the service market segmentation and product differentiation. The proposed delighter consumer needs criteria for the service market segmentation and product differentiation have been tested by the authors in one selected hotel in Vilnius. Methods used for the analysis: customer survey’( one-on-one interviews), mathematical-statistical methods for the analysis of survey data - CHITEST (to determine if hypothesized results are verified by an experiment), logistic regression (to estimate the parameters of a specific non-linear regression model coefficients and log likelihood coefficients). Model of hotel service elements-delighter consumer needs of selected market segments have been developed.